Peran Guru dalam Menangani Konflik Sosial antar Siswa di SDN 2 Mamben Daya - Rizal, Syamsur (FONDATIA, 2025)
Social conflicts among students are a frequent phenomenon in primary school settings and have the potential to disrupt the teaching–learning process and students’ social development, thereby positioning teachers as central actors who play a crucial role in preventing and resolving conflicts through pedagogical and socio-emotional approaches. This study aims to describe the role of teachers in handling social conflicts among students at SDN 2 Mamben Daya. A descriptive qualitative approach was employed, using in-depth interviews, participatory observations, and document studies as data collection techniques, with classroom teachers and the school principal who were directly involved in managing student conflicts serving as the research subjects. The findings show that teachers act as mediators, character builders, and facilitators of empathic communication, actively identifying potential conflicts, integrating cultural and religious values into problem-solving, and establishing collaboration with students’ parents. These strategies have proven effective in creating an inclusive and harmonious learning environment. The study concludes that the role of teachers in addressing social conflicts among students is not only curative but also preventive and educative, thereby requiring institutional support that includes teacher training, the strengthening of character education curricula, and school–family partnerships. These findings are expected to serve as a reference for the development of policies and educational practices based on conflict resolution in primary schools.